Opportunities for a Circular Bioeconomy in Rice Production - Runkle, Benjamin; Seyfferth, Angelia; Reid, Matthew; Reba, Michele; Limmer, Matt; Moreno-Garcia, Beatriz (Resource, 2023)
Amending soil with rice husk was the subject of a recent USDA project under the leadership of Dr. Angelia Seyfferth, along with colleagues at Cornell University and the USDA-ARS Delta Water Management Research Unit. In rice, increased silicon availability can reduce straight-head disorder, increase water and nitrogen use efficiency, and increase resistance to stress, pests, and disease. [...]returning rice husk to paddy soils could support rice growth in sustainable and climate-smart irrigation regimes that reduce water use and fertilizer application. The addition of silicon to the soil through husk amendment also reduces plant and grain uptake of the toxic element arsenic through several soil-root-plant mechanisms, which could reduce a burgeoning public health challenge for populations whose diets are high in rice. For those who want to explore new uses for rice husk, the Riceland Mill in Jonesboro, Arkansas, sells 50 lb (23 kg) bags of rice husk for just $7.50 each! ASABE member Benjamin Runkle, P.E., Department of Biological and Agricultural Engineering, University of Arkansas, Fayetteville, USA, brrunkle@uark.edu; Angelia Seyfferth, Department of Plant and Soil Sciences, University of Delaware, Newark, USA; Matthew Reid, Department of Civil and Environmental Engineering,